Experience in the surgical treatment of juvenile nasopharyngeal angiofibroma at the Hospital de Especialidades No. 2 "Lic. Luis Donaldo Colosio Murrieta", Mexican Social Security Institute, Ciudad Obregón, Sonora - Rubio-Espinoza, A. (2018)
Objective: To present our experience and assess the recurrence of juvenile nasopharyngeal angiofibroma after a surgical treatment (open versus endoscopic approach) in the country’s northwestern Department of Otorhinolaryngology. Materials and methods: An observational, retrospective, analytical study. The medical records of patients diagnosed with juvenile nasopharyngeal angiofibroma, who were treated at the Department of Otorhinolaryngology – Head and Neck Surgery of this institution from 2014 to 2017, were reviewed. Results: A total of 19 patients diagnosed with juvenile nasopharyngeal angiofibroma underwent a surgical procedure, out of which 14 had an open surgery and 5 an endoscopic one. Recurrence accounted for 50 % and 40 %, respectively, which was not statistically significant (p = 0.88). However, other variables were compared, such as the need for admission to the Intensive Care Unit (ICU), which was represented by 71 % in the case of the open approach and 20 % for the endoscopic approach, where a significant difference was found (p = 0.04). Conclusions: The study shows no statistically significant advantage of the endoscopic approach versus the open approach, but demonstrates less need for ICU admissions, which would reduce healthcare costs.